Effectiveness of Kegel Exercises on Perineal Wound Healing among Postpartum Women - Rosyida, Desta Ayu Cahya; Hidyatunnikmah, Nina (Universitas Islam Bandung, 2024)
Perineal wound refers to a laceration or wound that occurs along the birth canal (perineum) due to the delivery process. Wound healing is a method involved in replacing and repairing damaged tissue's capacity. This study aims to determine the effectiveness of Kegel exercises on perineal wound healing. It was a quasi-experimental study with one group pretest-posttest design conducted in March–May 2023. Forty-five women with perineal wounds at the Arosbaya Public Health Center, a reputable healthcare facility in Bangkalan, East Java province, Indonesia known for its comprehensive postpartum care, were selected as the study samples through a random sampling technique. The pre-test was done by observing the perineal wound before doing Kegel exercises. At the intervention stage, respondents did Kegel exercises daily for seven days. The post-test was carried out on day 7, and then observation of the perineum wound was carried out. Data were collected using an observation sheet. T-test was applied for the statistical tests. The study results show that after carrying out Kegel exercises, the majority of the 45 respondents experienced changes; namely, 25 people experienced good wound healing, and the remaining 20 experienced poor wound healing. The calculated t value was higher than the t table value (−16.523>−2.015) and had a significance value of <0.05 (0.000<0.05). This study's findings have practical implications for postpartum care, as they highlight the potential of Kegel exercises in promoting perineal wound healing, thereby enhancing the knowledge and practice of healthcare professionals and postpartum women.